Characterization of Nano- and Microstructures of Native Potato Starch as Affected by Physical, Chemical, and Biological Treatments - Mojo-Quisani, Antonieta; Licona-Pacco, Katiuska; Choque-Quispe, David; Calla-Florez, Miriam; Ligarda-Samanez, Carlos A.; Pumacahua-Ramos, Augusto; Huamaní-Meléndez, Víctor J. [UNESP] (MDPI, 2024)
Modifying starch allows for improvements in its properties to enable improved uses in food matrices, bioplastics, and encapsulating agents. In this research, four varieties of native potato starch were modified by acid treatment, enzymatic treatment, and ethanol precipitation, and their physicochemical, structural, thermal, and techno-functional characteristics were analyzed. According to FT-IR analysis, no influence of the modified starches on the chemical groups was observed, and by scanning electron microscopy (SEM), spherical and oval shapes were observed in the acid and enzymatic treatments, with particle sizes between 27 and 36 μm. In particular, the ethanolic precipitation treatment yielded a different morphology with a particle size between 10.9 and 476.3 nm, resulting in a significant decrease in gelatinization temperature (DSC) and more pronounced crystallites (XRD). On the other hand, the enzymatic treatment showed higher values for z-potential (ζ), and the acid treatment showed lower mass loss (TGA). Acid and ethanolic treatments affected the dough properties compared to native starches. The techno-functional properties showed a decrease in the water absorption index, an increase in the water solubility index, and varied swelling power behaviors. In conclusion, the modification of potato starches through acid, enzymatic, and ethanolic precipitation treatments alters their physicochemical properties, such as swelling capacity, viscosity, and thermal stability. This in turn affects their molecular structure, modifying morphology and the ability to form gels, which expands their applications in the food industry to improve textures, stabilize emulsions, and thicken products. Furthermore, these modifications also open new opportunities for the development of bioplastics by improving the biodegradability and mechanical properties of starch-based plastic materials.
Keywords: acid treatment; enzymatic treatment; ethanolic precipitation; modified starch; physicochemical characterization; structural; thermal